Tipos de demoras obstétricas em pacientes com condições potencialmente ameaçadoras à vida em uma maternidade de referência de Sobral-Ce - Araújo, Lívia Mara de (2022)
Objective: to identify the types of obstetric delays in patients with potentially life-threatening conditions in a reference maternity hospital in Sobral-CE. Method: cross-sectional research with a quantitative approach. Data collection took place in the wards of the Maternidade Sant'Ana sector from January to May 2022 with 108 puerperal women hospitalized in that sector who were in the puerperal period for up to 42 days and who suffered a potentially lifethreatening condition. The instrument for data collection was a questionnaire prepared by the author of the research, comprising: sociodemographic data, obstetric/prenatal/pilgrimage data, data on potentially life-threatening conditions and obstetric delays. Data were analyzed using Microsoft Excel 2019 and R version 4.1.0 software, and the frequency, mean and standard deviation of the variables were described. Results: There was a predominance of delay III, followed by delay I and finally delay II. As for the age of the mothers, they had an average of 29 years in a stable or married relationship, with an average of 13.29 years of study, brown and family income of up to one minimum wage. As for the sociodemographic aspects, there was a predominance of delay I regarding the marital status of stable union; delay II regarding schooling with an average of 11.78 years studied and delay III regarding brown race. Regarding the classification of obstetric delays according to potentially life-threatening conditions, they were classified as follows: women who had bleeding disorders: delays II and III predominated. While women with hypertensive disorders: presented delay I and III. With regard to carrying out a critical intervention, they presented delay III. In relation to potentially life-threatening conditions, including bleeding and hypertensive disorders and carrying out a critical intervention, there was a prevalence of delay III. Delays II and III emerged related to potentially life-threatening conditions regarding bleeding disorders and performing a critical intervention, which was significantly associated with delay III. Regarding the pilgrimage indicators, women who noticed intercurrence of pain had type II delay, with 2.8 times more chances of the patient experiencing delay in receiving care. Indicator related to type II delay was whether “Was there any interference in the journey to the maternity ward” in which there are 21.74 times more chances of pregnant women experiencing delay in receiving care (delay II), when they experience some interference in the journey until you reach the maternity ward. As for the time taken by patients who had type II delay, it obtained an average of 9.53 hours from the beginning of the search for care to hospitalization. It was found that the indicators “You were hospitalized at the first maternity hospital you sought” and the time from the beginning of the search for care until hospitalization had a significant association with the type II delay, with 6.69 times more chances of the patient who did not stay hospitalized in the first maternity that tried to have type II delay. The indicators that were significantly associated with type III delay were 'Being admitted to the first maternity hospital you sought', 'Being attended to at the reference maternity hospital in your region according to gestational risk', 'Having referral to the reference maternity hospital' and 'Time from the beginning of the search for assistance until admission (hours)'. It was evidenced that there are 2.73 times more chances of those who were not hospitalized in the first maternity hospital who tried to undergo type III delay. Conclusion: it is concluded that there is a predominance of delays III and I in the findings of this study, therefore, the reduction of delays, such as the provision of inputs and equipment, a better referral system and availability of transport could contribute to the reduction of CPAV, severe maternal outcomes, maternal near miss and even maternal deaths.